Akka in action - Roestenburg, Raymond; Bakker, Rob, (Software developer); Williams, Rob (Manning Publications, 2017)
Akka in Action shows you how to build message-oriented systems with Akka. This comprehensive, hands-on tutorial introduces each concept with a working example. You?ll start with the big picture of how Akka works, and then quickly build and deploy a fully functional REST service out of actors. You?ll explore test-driven development and deploying and scaling fault-tolerant systems. After mastering the basics, you?ll discover how to model immutable messages, implement domain models, and apply techniques like event sourcing and CQRS. You?ll also find a tutorial on building streaming applications using akka-stream and akka-http. Finally, you?ll get practical advice on how to customize and extend your Akka system.